Uwarunkowania instytucjonalne rozwoju rynku ubezpieczeniowego - Jędrzejczyk, Irena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The existing institutions contribute to the development of the insurance market in Poland, as well as to the growing input of the insurance sector into the country's development.The institutional conditions call for constant monitoring and in-depth research aimed at verification of the following theses:1. The way particular institutions perceive and evaluate their own activity is considerably different from the actual functions they perform. There is a discrepancy between the purposes for which the institutions have been established, and the reality.2. The world community, as well the European and national communities, cooperate with one another; as we function in one world, various risks of different degree and scope are elements of one, global risk.3. There is a connection between how efficient the institutions are performing their functions within the insurance sector, and the objectives of the state's economy and European policy.The capital conditions are among the most important institutional conditions for the development of the insurance market.Financial studies cannot be regarded as the only instrument for comprehensive analysis and explanation of how the insurance market is functioning because an insurance company is not merely a system of cash flow, financial flows and capital resources, as understood in the definition of a financial institution, but also a system of real economic resources and flows of goods and services. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 218-230